Pola Praktik Penyelesaian Tindak Pidana Anak di Lamongan Dalam Perspektif Restorative Justice: Studi Kasus Anak yang Berhadapan dengan Hukum di Lamongan - Anshori, Anshori (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
Protection of children is a constitutional obligation and for children is a constitutional right. In the context of children as national assets, protection for them is a necessity for the State. Then the incident of children in conflict with the law is also the scope of children who must be protected by the State, and in handling it, is it the same as adults who commit criminal acts. On the basis of this premise, research under the above title was conducted. Then this research is intended to portray legal practice, its relevance to the concept of justice restoration which has actually been adopted by the Child Protection Law with the terminology of diversion. In this study using the normative juridical method and collaborating with a sociological approach, then in the normative approach method, preceded by an inventory of positive laws governing child protection in the criminal justice system, then studying legal principles, in concreto legal discovery and the level of vertical synchronization. and horizontal. Then the sociological juridical approach is used to determine the implementation of child protection in the practice of the criminal justice system, where there are social aspects that influence the operation of law in society (law in action). The result of this research is to try to portray the concept of justice restoration as a model for solving children who are dealing with the law, with the reality of the law in its enforcement.